THE IMPACT OF USING EDUCATIONAL AID IN TEACHING FOREHAND AND BACKHAND SKILLS IN TENNIS FOR FEMALE STUDENTS - Ahmed Sadiq Niyazi; Zainab Sabri Hazim (Proximus Journal Publishing, 2025)
Researchers and educational specialists are continuously exploring effective educational methods and techniques, particularly in the context of motor learning principles and their applications in the educational process. Tennis, a highly popular sport, is valued by practitioners who enjoy mastering its skills. These skills require a solid foundation for optimal learning. The learning process is crucial as it establishes the basis for achieving sporting effectiveness. By employing a well-structured learning program that incorporates various modern educational methods and media, we can take into account the students' educational backgrounds, physical and mental abilities, and individual differences, ultimately leading to a higher level of skill performance.
Keywords: mental abilities; individual differences; educational aid; tennis